The Influence of Props-Based Learning Media Against Improved Construction Learning Outcomes and Building Utilities at SMK Negeri 4 Pariaman - Rani, Rani; Zuwida, Nidal (CIVED, 2023)
The This research was conducted based on the background of the unavailability of supporting learning media in Building Construction and Utility subjects, especially in the material of applying procedures for making detailed foundations, sloofs, columns and beams. This research aims to produce products that are valid, practical and effective and have an impact on improving learning outcomes in Building Construction and Utilities. This research uses the R&D research method using the 4D development model which consists of four stages, namely define, design, develop and disseminate. The instruments used in this research were learning media validation questionnaires for media and material experts, learning media practicality questionnaires for students, as well as learning media effectiveness test questions for students. The media validation results for detailed foundation, sloof, column and beam media show that the learning media can be categorized as very valid with a level of validity by media 1 of 85.45%, media expert 2 of 85.45%, expert media 3 of 87.27 %, material expert 1 was 85.71% with a very valid category; The practicality of the detailed media for foundations, sloofs, columns and beams based on student assessment was 89.87% in the very practical category; Furthermore, the effectiveness assessment was carried out by testing the N-Gain Score with a value of 36.6% in the quite effective category as well as testing the T-test. Students received a value of tcount > ttable or 5.812 > 1.741, which means that Ha was accepted and Ho was rejected. According to the results of the overall assessment of teaching aids media, the resulting learning media products were stated to be very valid, practical, and quite effective for use in supporting the learning process, as well as having a significant effect on improving learning outcomes in Construction and Building Utilities.